Constraints on the Origin of the Martian Dichotomy From Southern Highlands Marsquakes - Sun, Weijia; Tkalčić, Hrvoje (Geophysical research letters, 2025)
The Martian hemispheric dichotomy is delineated by significant differences in elevation and crustal thickness between the Northern Lowlands and Southern Highlands. Yet, its origin remains controversial. Here, we improve the signal‐to‐noise ratios and determine the locations of the low‐frequency marsquakes recorded during the InSight mission. We find a new cluster of marsquakes in Terra Cimmeria, Southern Highlands, in addition to those previously located in Cerberus Fossae, Northern Lowlands. Using the spectral ratio method, we estimate the quality factor Q in the range 481–543 for Terra Cimmeria versus 800–2,000 determined for Cerberus Fossae. The attenuation difference might be linked to the temperature differences between the two hemispheres, along with more vigorous convection beneath the Southern Highlands. These seismological observations, together with geochronological constraints of giant impacts, reinforce the “endogenic” hypothesis that mantle convection causes the crustal dichotomy. Plain Language Summary The Martian hemispheric dichotomy is characterized by a contrast in elevation and crustal thickness between the Northern Lowlands and Southern Highlands. The origins of this dichotomy have been a subject of debate, with various hypotheses proposed. Through the analysis of InSight marsquakes, we have made significant progress in understanding this phenomenon. Our study focuses on improving the signal‐to‐noise ratios and accurately locating some low‐frequency marsquakes. As a result, we find a new cluster of marsquakes in Terra Cimmeria, located in the Southern Highlands, in addition to the previously identified cluster in Cerberus Fossae, situated in the Northern Lowlands. As a result, we estimate the attenuation quality factor Q of 481–543 for Terra Cimmeria, which is significantly lower than the 800–2,000 determined for Cerberus Fossae. This attenuation disparity could be attributed to temperature variations between the two hemispheres and more vigorous convection beneath the Southern Highlands. These findings, supported by geochemical analysis of Martian meteorites, provide valuable in situ seismological observations that support the “endogenic” hypothesis, suggesting that mantle convection plays a crucial role in forming the Martian crustal dichotomy. Key Points We employ 3‐D P‐wave polarization analysis in the optimal frequency band to locate a cluster of six marsquakes in the Southern Highlands The quality factor 480–540 in the south versus 800–2,000 in the north indicates higher temperature and lower viscosity in the southern mantle Seismic attenuation aligns with geochronological constraints of giant impacts supporting mantle convection as a cause of the dichotomy